2019
DOI: 10.3390/ijms20040855
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Chinese Chestnut (Castanea mollissima Blume) in Response to Dryocosmus kuriphilus Yasumatsu Infestation

Abstract: Chinese chestnut (Castanea mollissima Blume) can be infested by Dryocosmus kuriphilus Yasumatsu, resulting in gall formation and yield losses. Research on the control of gall wasps using genomics approaches is rarely reported. We used RNA-seq to investigate the dynamic changes in the genes of a chestnut species (C. mollissima B.) during four gall-formation stages caused by D. kuriphilus. A total of 21,306 genes were annotated by BLAST in databases. Transcriptome comparison between different gall-formation stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The two most highly expressed chitinases were concordantly differentially and more highly expressed in mature galls (Mature > Growth and Early stages) and in older normal bud tissues (S5 > S4). Similar late stage host-plant chitinase expression was also observed in chestnut gall tissues attacked by another cynipid, Dryocosmus kuriphilus [87].…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…The two most highly expressed chitinases were concordantly differentially and more highly expressed in mature galls (Mature > Growth and Early stages) and in older normal bud tissues (S5 > S4). Similar late stage host-plant chitinase expression was also observed in chestnut gall tissues attacked by another cynipid, Dryocosmus kuriphilus [87].…”
Section: Resultsmentioning
confidence: 53%
“…We found marked divergence in oak gene expression between galled and ungalled host tissues, as observed in cynipid-induced chestnut galls and phylloxera-induced galls on grape vines [25,87]. The clear developmental trajectory of gall tissues also contrasted strongly with the pattern observed in normally developing ungalled buds, which showed little transcriptomic differentiation between recognised morphological stages through budburst, but clear differentiation between opening buds and fully open leaves.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Because transcriptome data is the result of high-throughput sequencing, which aims at the global gene expression patterns, whereas qRT-PCR analysis is directed to the individual gene on the basis of the specific gene primers, the slight difference for individual gene on the basis of the two methods is reasonable. The different expression profiles shown by these two approaches usually occur [39], and the results of qRT-PCR should be more accurate. Overall, these results indicated that our RNA-seq data were reliable and the error was also within the reasonable range.…”
Section: Validation Of Rna-seq Data By Quantitative Real Time (Qrt)-pcrmentioning
confidence: 99%
“…Aphis galls on Rhus chinensis accumulate gallotannin, and genes involved in gallotannin biosynthesis [99], gallic acid synthesis [98], and lignin biosynthesis [97] have been identified. In the developing gall of the chestnut gall wasp, Dryocosmus kuriphilus, on the Chinese chestnut, Castanea mollissima, the expression of genes related to metabolic processes, such as phenylpropanoid biosynthesis, secondary metabolism, and plant-pathogen interactions, was altered compared to that of non-infested leaves [100]. Galls induced on elm leaves by a gall-inducing aphid, Tetraneura akinire, were shown to express the genes encoding lignocellulose synthase, suggesting the reinforcement of cell walls to improve resistance to damage by the aphid [101].…”
Section: Changes In the Expression Patterns Of Genes Involved In The Biosynthesis Of The Metabolic Process During Gall Formationmentioning
confidence: 99%